(untitled) (Annals of Medical Research, 2021)
Aim: Using Clomiphene citrate (CC) plus letrozole combination to determine the effect of follicular diameter on pregnancy outcomes in CC resistance Polycystic ovary syndrome (PCOS) patients during intra uterine insemination cycles. Material and Methods: The records of infertile patients who presented to the outpatient clinic were retrospectively analysed. PCOS was diagnosed in 536 (23%) patients, 71 (18%) of whom had CC-resistant PCOS using CC plus letrozole. The patients were divided into two groups; follicular diameter 17-19 mm (group 1, n = 31) and 20-22 mm (group 2, n = 40).Results: The pregnancy rate in group 1 was 20% (6/30), the abortion rate was 17% (1/6), and the multiple pregnancy rate was 17% (1/6). In group 2, the pregnancy rate was 17% (7/41), the abortion rate was 14% (1/7) and the multiple pregnancy rate was 14% (1/7). There was no statistically significant between-group difference in the pregnancy (p =0.3), abortion (p = 0.8) or multiple pregnancy rates (p =0.8).Conclusion: In PCOS patients with CC plus letrozole and intra uterine insemination ovulation induction, pregnancy rate is not related to follicular size between 17-22 mm on hCG day. Although there was no direct relationship between follicular size and endometrial thickness, it was found that delaying HCG was not significant for better results.